Implementasi Evaluasi Kurikulum Sekolah (Studi Kasus Sekolah Dasar di Kabupaten Kudus) - Niam Wahzudik (Universitas Sebelas Maret, 2020)
Curriculum evaluation activities as an important part of curriculum management must be carried out by each education unit. The school's knowledge and understanding of the concept and implementation of curriculum evaluation has an influence in efforts to ensure the success of curriculum evaluation. The purpose of this study is to describe the process of curriculum evaluation at the level of basic education in Kudus Regency in terms of aspects of school understanding of the concept and urgency of curriculum evaluation, evaluation model selection, curriculum evaluation dimensions, school needs that support curriculum evaluation activities. Research uses the case study research method that was conducted at SD Negeri 1 Wergu Kulon, Kudus Regency. Research informants consisted of school principals and teachers. Data collection by interview. Data analysis was performed descriptively qualitative. The results showed that in general schools understood the concept and urgency of curriculum evaluation in schools.